Isolation, Structure Elucidation, and (Bio)Synthesis of Haprolid, a Cell‐Type‐Specific Myxobacterial Cytotoxin. Issue 34 (12th July 2016) - Steinmetz, Heinrich; Li, Jun; Fu, Chengzhang; Zaburannyi, Nestor; Kunze, Birgitte; Harmrolfs, Kirsten; Schmitt, Viktoria; Herrmann, Jennifer; Reichenbach, Hans; Höfle, Gerhard; Kalesse, Markus; Müller, Rolf
Abstract: Myxobacteria are well‐established sources for novel natural products exhibiting intriguing bioactivities. We here report on haprolid (1 ) isolated from Byssovorax cruenta Har1. The compound exhibits an unprecedented macrolactone comprising four modified amino acids and a polyketide fragment. As configurational assignment proved difficult, a bioinformatic analysis of the biosynthetic gene cluster was chosen to predict the configuration of each stereocenter. In‐depth analysis of the corresponding biosynthetic proteins established a hybrid polyketide synthase/nonribosomal peptide synthetase origin of haprolid and allowed for stereochemical assignments. A subsequent total synthesis yielded haprolid and corroborated all predictions made. Intriguingly, haprolid showed cytotoxicity against several cell lines in the nanomolar range whereas other cells were almost unaffected by treatment with the compound. Abstract : The macrolactone haprolid was isolated from Byssovorax cruenta . Bioinformatic analysis of the haprolid biosynthetic gene cluster aided stereochemical assignments based on the hybrid polyketide synthase/nonribosomal peptide synthetase origin of the compound. Total synthesis corroborated all predictions. Haprolid showed cytotoxicity against several cell lines in the nanomolar range whereas other cells were almost unaffected.